Development of Milkfish (Chanos chanos) Cracker Start-up Business in the Home Industry "Poklahsar Usaha Bunda" - Boy Riza Juanda; Iwan Saputra; Hanisah (Eumpang Breuh : Jurnal Pengabdian Masyarakat, 2022)
Kuala Langsa is a village located in the District of West Langsa, Langsa City, which has a large potential for fishing. One of the activities carried out in fish processing at this time is the processing of milk fish into kerupuk ikan bandeng products which is carried out on a home industry scale. Kerupuk ikan bandeng industry is currently the only fish cracker industry in Langsa City and is start up business that has just been carried out by a home industry in the Langsa village, namely "Poklahsar Bunda Usaha" so that the kerupuk ikan bandeng business has potential great to be able to develop. Program Kemitraan Masyarakat Stimulus was designed as a form of response to the problem of the availability of inadequate production facilities and poor business management. Program Kemitraan Masyarakat Stimulus is implemented with a pattern of education and training and mentoring. With Program Kemitraan Masyarakat Stimulus (PKMS), now home industri Poklahsar Usaha Bunda already has a unit of flour dough mixer for making milk fish crackers, has a P-IRT certificate, has a more attractive packaging label and is able to expand its network and the marketing area for milkfish crackers.